Nutritional and anti-nutritional values of multipurpose trees used in agroforestry systems - Osuji, P.O. (Australian Centre for International Agricultural Research, 1994)
Multipurpose trees (MPTs) improve the utilization of poor quality roughages. In addition to their feed value, MPTs contribute to the environment, e.g. by conserving soil. However, some MPTs contain anti-nutritional factors which reduce their nutritive value. Trials in which gas production and rumen degradation rates were studied indicated that MPTs increased the rates of degradation of fibrous feeds, their rate of passage and the efficiency of microbial protein supply. The effects of extracts of several MPTs on pure cultures of Fibrobacter succinogenes, Ruminococcus flavefaciens and R. albus were Reported. Acacia angustissima suppressed the growth of Ruminococcus and slowed the growth of other bacteria. Dry matter yields were significantly increased when leucaena or gliricidia were intercropped with maize/cassava or napier grass in agro-forestry systems. It was concluded that the improved milk production resulting from such systems has many social benefits for the smallholder and his family.